Reframing Contractual Freedom in Cross-Border Commercial Agreements: Legal Challenges of Standard Terms and Global Consumer Protection - Rismaya Maharsanthy, Yovanka; Susilowati, Etty; Rattanapun , Supot (Journal Evidence Of Law, 2025)
The increasing prevalence of standard clauses in international commercial agreements has intensified normative tensions between the principle of freedom of contract and the imperative of global consumer protection. This study investigates the legal ramifications of such clauses in cross-border transactions, with particular emphasis on business-to-consumer (B2C) contracts marked by pronounced bargaining power asymmetries. Employing a normative legal methodology combined with comparative analysis, the research demonstrates that standard clauses are frequently drafted unilaterally, lack sufficient transparency, and impose liability limitations that operate to the detriment of consumers. The analysis further reveals significant regulatory fragmentation across jurisdictions and the absence of coherent international standards capable of ensuring legal certainty and affording equal protection to consumers. In response, the study advances a reconceptualization of the principle of freedom of contract in the transnational arena, underscoring the primacy of substantive justice, the necessity of transparency in information disclosure, and the enforceability of consumer rights. As a practical contribution, it recommends the establishment of a harmonized international legal framework for the regulation of standard clauses, grounded in the principles of minimum protection and cross-jurisdictional justice. This research thereby seeks to contribute to the evolution of international contract law toward greater responsiveness to the challenges of globalization and the exigencies of consumer protection in the digital economy.